An analysis of the time duration of ground strokes in Grand Slam men's singles using the computerised scorebook for tennis - Takahashi, H.; Wada, T.; Maeda, A.; Kodama, M.; Nishizono, H. (International Journal of Performance Analysis in Sport, 2008)
The purpose of this study was to analyse the time duration of ground strokes in various court surfaces in men's singles tennis. We used the computerised scorebook for tennis to collect the data from the three Grand Slam men's singles tennis tournaments (French Open, Wimbledon, U.S. Open) held in 2003 and 2004. The total number of study matches was 41. The time duration of ground strokes was analysed from the data. The factor of the player's situation showed a significant difference (p<0.01). The time duration of ground strokes on the server was 1.33±0.01 s and on receiver was 1.38±0.01 s. This result was influenced by the difference of tactics in service games and return games. The server has the advantage due to starting the rally by means of the serve. It leads the server to play more aggressively than the receiver.